PSIKOLOGI POSITIF: STUDI MENGENAI KEBAHAGIAAN DAN KEKUATAN MANUSIA - Seralarat, Kornelis (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2012)
Positive Psychology is a scientific study of human strength and virtue. Positive Psychology, as an umbrella term and a movement, focuses on happiness, positive health, resilience, growth, and psychological well-being. The scientists and practitioners of Positive Psychology believe that an individual, through Positive Psychology, can develop engagement and meaning in his life by knowing, understanding and applying his strength in meaningful ways in order to achieve happiness and well-being. This article presents a short history, the meaning and the purpose of Positive Psychology and its main themes such as happiness, well-being and human strength as well as the benefits of the interventions and applications of positive psychology in schools and clinical settings.